PEMENUHAN HAK ANAK ASUH PADA PANTI ASUHAN DI PANTI ASUHAN YATIM AS SIDIQIYAH SIAK - Astri Adillah; Hayatul Ismi; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The orphanage is designed to be a temporary shelter that provides protection for the rights of children as representatives of parents in meeting mental and social needs so that they have the opportunity to develop themselves until they reach a mature level of maturity, able to act as individuals and citizens in community life, able to live decent and independent and do not depend on others after leaving the orphanage later. The purpose of writing this thesis, namely; First, To Know the Fulfillment of the Rights of Foster Children at the Orphanage in the Orphanage of Sidiqiyah Siak Orphanage, Second, To Know the Obstacles Faced by the Orphanage of Sidiqiyah Siak Orphanage in Fostering the Rights of Foster Children.This type of research is sociological juridical. Data sources used are primary data, secondary data and tertiary data. Data collection techniques are by questionnaire, interview and literature study. Data analysis uses qualitative data analysis.The results of this study can be drawn several conclusions, First, the fulfillment of the right to shelter, education, food and drink, medication, and compassion have been given. Second, children's rights have not yet been fulfilled the freedom of children to return home, transportation facilities, possession of passbooks and mobile phones, guarantees and routine health services, work skills training, and written rules / discipline / sanctions for the benefit and good of foster children. Third, the obstacles in fulfilling the rights of foster children are more directed to the lack of interest in foster children in the development of skills, manners and character that is not good, as well as the lack of knowledge of the orphanage regarding guidelines for the fulfillment of the rights of foster children in the orphanage. Author's suggestion, that in the future orphanages pay more attention to fulfilling the rights of foster children and motivate foster children to increase awareness of the importance of skills development activities.Keywords: Fulfillment of Rights - Foster Children - Orphanages